Effect of condylar chondrocyte exosomes on condylar cartilage osteogenesis in rats under tensile stress - Shi, Yuan; Shao, Jiaqi; Zhang, Zanzan; Zhang, Jianan; Lu, Haiping (Frontiers in Bioengineering and Biotechnology, 2022)
Background: Functional orthoses are commonly used to treat skeletal Class II malocclusion, but the specific mechanism through which they do this has been a challenging topic in orthodontics. In the present study, we aimed to explore the effect of tensile stress on the osteogenic differentiation of condylar chondrocytes from an exosomal perspective. Methods: We cultured rat condylar chondrocytes under resting and tensile stress conditions and subsequently extracted cellular exosomes from them. We then screened miRNAs that were differentially expressed between the two exosome extracts by high-throughput sequencing and performed bioinformatics analysis and osteogenesis-related target gene prediction using the TargetScan and miRanda softwares. Exosomes cultured under resting and tensile stress conditions were co-cultured with condylar chondrocytes for 24 h to form the Control-Exo and Force-Exo exosome groups, respectively. Quantitative real time PCR(RT-qPCR) and western blotting were then used to determine the mRNA and protein expression levels of Runx2 and Sox9 in condylar chondrocytes. Results: The mRNA and protein expression levels of Runx2 and Sox9 in the Force-Exo group were significantly higher than those in the Control-Exo group (p < 0.05). The differential miRNA expression results were consistent with our sequencing results. Bioinformatics analysis and target gene prediction results showed that the main biological processes and molecular functions involved in differential miRNA expression in exosomes under tensile stress were biological processes and protein binding, respectively. Kyoto Gene and Genome Data Bank (KEGG) pathway enrichment analysis showed significant enrichment of differentially expressed miRNAs in the mTOR signaling pathway. The differentially expressed miRNAs were found to target osteogenesis-related genes. Conclusion: These results suggest that stimulation of rat condylar chondrocytes with tensile stress can alter the expression levels of certain miRNAs in their exosomes and promote their osteogenic differentiation. Exosomes under tensile stress culture conditions thus have potential applications in the treatment of Osteoarthritis (OA).